(3GdfXGe GdbGfhfi dYbhO GdeSGYOI Ydi GdENUGH GdHTQi habkG ddbGfhf GdeOfi GdeUQi (B/ s - (3agje YHOGdEdg YHOGdYRjR GdTGjYs; (3eMeO TcQi SQhQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2019)
(3Ef Jchjf GdCSQI h GdMUhd Ydi GdChdGO(B: (3Mb JcdaI cd GdOSGJjQ h GdehGKjb GdOhdjI(B: (3h JbfjGJ GdeSGYOI Ydi GdENUGH gi GdMdhd GdWHjI GdJbfjI GdJi LGOJ HgG GdYbdjI GdHTQjI deSGYOI TQjMI ef GdeJRhLjf ddJZdH Ydi CKGQ GdYbe h VYa GdNUhHI(B: (3HYO Cf cGfJ JbOe NOeGJgG ai gPG GdLGfH HGdhLg GdSdHi(B: (3h JQc gPg GdJbfjGJ deMOOGJgG GdYdejI(B: (3jLYdgG MdhdG LRFjI YjfjI(B: (3h CeGe MbjbI JQGLi CKGQgG(B: (3h JCKjQgG Ydi GMcGe fSH GdCTNGU(B: (3JHdhQJ GdedGMXI GdJi GfWdb efgG GdHGMK(B: (3GdJi JMhdJ Gdi SDGd eaGOI(B: (3eOi caGjI GdbhGYO GdYGeI GdhGQOI ai GdbGfhf GdeOfi Ydi GSJjYGH GdYdGbGJ GdYbOjI GdJi JfTFgG gPg GdYbhO(B. (3cGf gfGc YfUQGf jSgeGf ai JYbjO GdeTcdGJ GdbGfhfjI deSJYedi gPg GdJbfjGJ(B: (3JeKd GdChd SQYI JWhQ GdJbfjGJ ehVhY GdOQGSI(B: (3h JTYH MdhdgG(B: (3GdCeQ GdPi WQM GacGQG h WQbG LOjOI Mhd Jchjf GdCSQI h GdMUhd Ydi GdChdGO(B: (3CeG GdYfUQ GdKGfi(B: (3cGf ef WHjYI Yed gPg GdJbfjGJ(B: (3EP fLO Gf aUdG bO MUd Hjf NQhL GdMjhGfGJ GdefhjI h GdJbGFgG HGdHhjVI(B: (3GVGa HOhQg GdYOjO ef GdeTcdGJ GdbGfhfjI(B: (3dG SjeG Gf GdeQMdJjf cGfJG JMOJGf ai hbJ hGMO ai GdENUGH HUhQI WHjYjIs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2019.s
(3HHdjhLQGajG(B: (3UaMGJ (B302-330.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdeSDdjI GdWHjIs; (3CWaGd GdCfGHjHs; (3GdNdGjG GdJfGSdjIs; (3GdehGO GdEfLGHjI s; (3YbhO GdENUGHs; (3GfLGM GdMeds; (3GSJFLGQ GdCQMGes; (3GdeGfMs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs